Analisis Performa Motor BLDC 4000W pada Sepeda Motor Listrik Konversi - Candra, Adam Fadillah (JEECAE (Journal of Electrical, Electronics, Control, and Automotive Engineering), 2025)
This study discusses the performance analysis of a 4000W Brushless Direct Current (BLDC) motor used in a converted electric motorcycle as an environmentally friendly transportation alternative. The purpose of this research is to determine the performance characteristics of the BLDC motor through experimental testing using the dyno test method. The test was conducted ten times, with three valid data samples collected using a BRT 50L Dyno Test device. The measured parameters included torque (Nm), rotational speed (rpm), and output power (kW). The results showed that the maximum torque produced was 21 Nm at 1936 rpm, the maximum power reached 8.28 kW at 3921 rpm, and the highest speed achieved was 97.94 km/h. These findings indicate that the 4000W BLDC motor performs well in generating thrust at low speeds and maintains stable power efficiency at medium-speed ranges. Overall, the obtained performance demonstrates that the 4000W BLDC motor is feasible to be used as the main driving system for converted electric motorcycles intended for daily mobility needs.